lncRNA H22954 Inhibits Angiogenesis in Acute Myeloid Leukemia through a PDGFA-dependent Mechanism - Li, Xuewei; Rong, Jianjie; Li, Tianyu; Zhou, Yujing; Qi, Xiaofei (Recent Patents on Anti-Cancer Drug Discovery, 2022)
Background: Angiogenesis is a hallmark of cancer, which is regulated by diverse factors, including long non-coding RNAs (lncRNAS). Our previous study showed that the long non-coding RNA H22954 inhibits tumor growth, albeit whether it is involved in the angiogenesis of cancer re-mains unknown. Objectives: This study aimed to investigate the role of lncRNA H22954 in angiogenesis of acute myeloid leukemia (AML) and the underlying molecular mechanism. Methods: Bioinformatics analysis was conducted to screen the targeted molecule of H22954. Western blot and ELISA analysis detected PDGFA protein expression, and RT-qPCR detected H22954 and PDGFA expression in cell lines and AML samples. Dual-luciferase reporter gene assay and half-life assay were applied to validate the relationship between H22954 and PDGFA. The functional experi-ment was conducted to investigate the role of H22954 in tube formation. Results: Overexpression of H22954 inhibited angiogenesis in mouse xenograft tumors and cultured acute myeloid leukemia (AML) cells. Bioinformatics analysis and luciferase assay revealed that H22954 targeted the 3’ untranslated region (UTR) of the platelet-derived growth factor subunit A (PDGFA) gene. In transfected cells, H22954 overexpression reduced PDGFA expression and protein levels. Tube formation was rescued following the addition of exogenous human PDGFA to the con-ditioned medium from cells overexpressing H22954. The expression of H22954 in K562 cells re-duced the half-life of PDGFA mRNA. Furthermore, H22954 expression was inversely correlated with PDGFA expression in patient samples. Conclusion: These findings indicate that H22954 inhibits angiogenesis in AML through the down-regulation of PDGFA expression. Administering recombinant lncRNA H22954 may be a therapeutic approach for patients with AML.
Keywords: acute myeloid leukemia